Pseudaeginella telukrimau sp. n., a new species of caprellid (Crustacea: Amphipoda) from Malaysia - Lim, Jacqueline Hui Chern; Azman, Bin Abdul Rahim; Takeuchi, Ichiro; Othman, Bin Haji Ross (Zootaxa, 2017)
A new species of caprellid, Pseudaeginella telukrimau (Amphipoda: Senticaudata: Caprellidae) was discovered from Pulau Besar, Johor in Malaysia. This species was collected from a coral reef off Teluk Rimau. Species of Pseudaeginella are unique in terms of a very small/sometimes absent mandibular molar and the numerous projections on its pereonites. Pseudaeginella telukrimau is distinguishable by its paired mid-dorsal projections on pereonites 2 to 5, 1 ventrodistal triangular projection on pereonite 4, and gnathopod 2 ischium with 1 large trapezoid projection.